Neurogenic potential of human amniotic fluid cells derived from full-term gestation - A Hamid, Adila (2020)
Neurodegenerative diseases (ND) are recognized as one of the main sources of disability globally that causes burden to the patients, families and society. In most cases, ND are caused by neuronal dysfunction and progressive neuronal cell death. Unfortunately, there is no treatment to cure ND. Currently, neurotransplantation to replace the lost neurons is the hope for ND treatment. It is essential to generate neurons or neural stem cell (NSC) with therapeutic potential in vitro for treating ND, and finding the best suitable stem cells with neurogenic potential is, therefore, important. Highly potent stem cells from human mid-term amniotic fluid (AF) have garnered much attention as cells with broad multipotency, non-tumorigenic upon transplantation with less ethical concern and are neurogenic. However, procurement of AF at mid-term imposes certain risks to the mother and the foetus. Alternatively, being merely discarded, AF could also be collected at full-term during delivery to isolate amniotic fluid stem cells (AFSCs). This study aimed to establish AFSCs from AF collected from human full-term pregnancies during delivery (caesarean section) and unravel their neurogenic potential. Full-term (38-40 weeks gestation) AF were cultured in vitro in Amniomax medium and were then characterized with growth kinetic, population doubling time, panels of pluripotency and stemness markers and morphometric analysis. The spontaneous differentiation capacity was assessed by their ability to form embryoid bodies (EBs). The ability of the cells to undergo osteogenic, adipogenic, chondrogenic and neurogenic were also demonstrated in this study. The senescence of AFSCs were assessed by β-galactosidase staining and expression of senescence associated markers by RT-qPCR. To assess the neurogenic potential, AFSCs were subjected to monolayer adherent neurodifferentiation protocol and expression of early (Nestin), post-mitotic (Tuj1), matured (MAP-2) and functional neuronal markers (VGLUT1, SYP, SYPR, ChAT and TH) were determined by RT-qPCR and immunocytochemistry (ICC). In this study, transdifferentiation of AFSCs into NSCs were assessed by the expression of NSCs specific markers through ICC and RT-qPCR (Nestin, Sox-1 and Sox2). The generation of NSCs was validated by the ability of the cells to form neurospheres, the multicellular aggregates of NSCs in low attachment plate. In this study, full-term AFSCs were observed to show a high proliferative capacity with expression of pluripotency and stemness markers and able to differentiate into adipogenic, osteogenic, chondrogenic and neurogenic. Full-term AFSCs showed sign of senescence at P6. Full-term AFSCs able to form good quality EB. Upon monolayer neurogenic induction, AFSCs expressed neuronal marker according to different stages of neurogenesis in the brain. Transdifferentiated AFSCs expressed NSC specific markers (Nestin, Sox-1 and Sox2) and form neurospheres of appropriate size. These results clearly suggest full-term AFSCs as the potential stem cells that might be useful for future therapeutic potential, particularly as the source for neuro-transplantation in treating ND.